IMPLIKASI TANGGUNG JAWAB SOSIAL DAN LINGKUNGAN TERKAIT POTENSI DUGAAN KEJAHATAN KORPORASI: STUDI CONTENT ANALYSIS PADA PT LAPINDO BRANTAS INC. - Waya Muthia Wardhani; Fidelis Arastyo Andono (Jurnal Akuntansi Bisnis, 2018)
Management actions, which are supported by the implementation of corporate governance, is crucial in the decision making for any corporate actions. But in many occasions, the management took the decision to neglect the environment and social responsibility and set aside long-term goals of the company. On May 29, 2006 in the drilling area of PT Lapindo Brantas Inc. (Lapindo) located in Porong, Sidoarjo, an incident in which is one of the drilling well releases gas and mud. This case happened because the company allegedly shirking the implementation of social and environmental responsibility of theirs.The purpose of this study was to analyze the implementation of the activities of social and environmental responsibility of a company, and then connect the involvement of social environmental responsibility with the potential of alleged corporate crime. Using the content analysis method, the results showed that social and environmental responsibility of a company is very important to be implemented. In addition, management as manager of the company must always run actions guided by the principles of good governance. If the principles of good governance are not implemented by management, corporate actions whether intentional or not, will be more vulnerable and has the potential to intersect with corporate crime.Keywords: social and environmental responsibility, corporate crime, the principles of good governance